The science and politics of work disability prevention - MacEachen, Ellen (New York, NY : Routledge, 2019)
The rising cost of illness and disability benefits are one of today's biggest social and labour market challenges. The promise of activation-oriented work disability policies was labour market engagement for all people, regardless of illness, injury or impairment. However, the reality has been more complex. The Science and Politics of Work Disability Policy addresses social and political economic contexts driving state work disability reform in 13 countries. In this first attempt to explain the history and future of work disability policy, this book asks new questions about work disability policy design, focus, and effects. It details how work disability policies have evolved with jurisdictions, why these take their current shape, and where they are heading. The well positioned authors draw on their insider knowledge and expertise in law, medicine, and social science to provide detailed case studies of their jurisdictions. This pathbreaking volume will be of interest to social security system policy makers, scholars, and students in the health and social sciences.
Work Disability Prevention in the Netherlands: A Key Role for Employers; Angelique DeRijk Chapter 15. The Rise and Fall of Income Replacement Disability Benefit Receipt in the United Kingdom: What are the Consequences of Reforms?; Ben Barr & Philip McHale PART 4: CHALLENGES AND OPPORTUNITIES FOR WORK DISABILITY POLICY Chapter 16. Science, Politics and Values in Work Disability Policy: A Reflection on trends and The Way Forward; Ellen MacEachen & Kerstin Ekberg INDEX
OCLC-licensed vendor bibliographic record.
Keywords: People with disabilities -- Employment; Industrial safety; Social security; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General